Advances in organometallic chemistry - Stone, F. Gordon A. (Francis Gordon Albert), 1925-; West, Robert, 1928- (Advances in organometallic chemistry, 1996)
This widely acclaimed serial contains authoritative reviews that address all aspects of organometallic chemistry, a field which has expanded enormously since the publication of Volume 1 in 1964. Almost all branchesof chemistry now interface with organometallic chemistry--the study of compounds containing carbon-metal bonds. Organometallic compounds range from species which are so reactive that they only have a transient existence at ambient temperatures to species which are thermally very stable. Organometallics are used extensively in the synthesis of useful compounds on both large and small scales. Industrial processes involving plastics, polymers, electronic materials, and pharmaceuticals all depend on advancements in organometallic chemistry.